(untitled) (DIMENSI: Journal of Architecture and Built Environment, 2016)
Concentration has an important role in our life, especially in order to get a quality and productivity in working. With concentration we can achieve the maximum and faster result in our work. Some ways to improve concentration that being researched here is by arranging the wall color and the lamp color temperature of the room. The color used as wall color in this research was the blue 9.8B, 7.4/5.6; and the orange 8.1YR, 8.7/3.7 of the Munsell color palette. Whereas the room lighting was the fluorescent lamp in 6500K (cool daylight) and 2700K (warm white) color temperature. Respondents of this research were 117 undergraduate students, the average GPA was 3.28; and 20,26 years as the mean age. The concentration and cognition tests are the Army Alfa test and IST subtest 9 that conducted in the room with different condition. Found in this research that the blue with cool daylight lamp has significant impact to concentration in 2,526 Lickert scale; and that orange with cool daylight lamp has correlation 0.781 to cognition result; but the other conditions have no significancy toward concentration and cognition